SQ HDM SLIT-tablet (ALK) in treatment of asthma – Post hoc results from a randomised trial - de Blay, F.; Kuna, P.; Prieto, L.; Ginko, T.; Seitzberg, D.; Riis, B.; Canonica, G.W. (Respiratory medicine, 2014)
In a double-blind, placebo-controlled trial (EudraCT identifier: 2006-001795-20), the standardised quality (SQ) house dust mite (HDM) sublingual immunotherapy (SLIT)-tablet (ALK, Denmark) was investigated. The trial included 604 subjects, ≥14 years, with mild-moderate HDM allergic asthma. Subjects were randomised 1:1:1:1 to 1, 3 or 6 SQ-HDM or placebo once daily. The primary endpoint was reduction in inhaled corticosteroid (ICS) after one year. ICS reduction, asthma quality of life questionnaire (AQLQ) and asthma control questionnaire (ACQ) score was analysed post hoc in a subgroup with daily ICS use of 400–800 μg and ACQ score of 1–1.5, corresponding to partly controlled asthma (N = 108). The trial met its primary endpoint. In the subgroup, the difference between placebo and 6 SQ-HDM in change from baseline in daily ICS use was 327 μg (p < 0.0001), while it was 0.52 (p = 0.010) for AQLQ. The treatment effect on ICS reduction and AQLQ was increased for the subgroup versus the residual population (ICS reduction: p < 0.001); AQLQ: p = 0.044). In this subgroup, including only patients with partly controlled asthma, the benefit of 1 year of treatment with SQ HDM SLIT-tablet was significantly higher than for the less severe full population, both in terms of increased asthma control and improved quality of life.